NONSURGICAL ENDODONTIC MANAGEMENT OF CUTANEOUSLY DRAINING ODONTOGENIC SINUS - Qazi, Shahid Shuja; Manzoor, Manzoor Ahmed; Qureshi, Rizwan; Arjumand, Bilal; Hussain, Syed Muzammil; Afridi, Zulqarnain (Journal of Ayub Medical College Abbottabad, 2006)
Odontogenic cutaneous sinus tract is a rare but well documented condition. It is usually misdiagnosed as a local skin lesion and maltreated by systemic antibiotics and/ or surgical excision with eventual recurrence. This is because the primary etiology is incorrectly determined. We came across a 38 year old patient who presented with a cutaneous lesion on her left cheek with frequent purulent discharge and was not responding to systemic antibiotics. The case history, diagnosis and management of this condition is presented here. Key words: Nonsurgical endodontic therapy, odontogenic, cutaneous sinus